(untitled) (World Bulletin of Management and Law, 2026)
Migration governance and the regulation of population mobility have become important elements of modern state policy in the context of increasing global migration flows. This article examines the evolution of legal migration governance and the development of migration policy in Uzbekistan. The study focuses on the institutional and legal mechanisms regulating entry and exit processes, as well as the transformation of migration management in recent years. Based on the analysis of national legislation and policy reforms, the article identifies key stages in the development of migration regulation. The findings suggest that Uzbekistan has gradually strengthened its legal and institutional framework for managing migration processes, aiming to ensure orderly mobility while supporting socio-economic development and international cooperation in migration governance.